THE ROLE OF TECHNOLOGY IN THE GREEN ECONOMY: A LITERATURE REVIEW ON INNOVATION AND SUSTAINABILITY - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This research aims to review the role of technology in the green economy with a focus on innovation and sustainability. Through a literature review, this research explores various forms of green technologies such as renewable energy, energy efficiency, and waste management technologies, and their benefits in reducing environmental impacts and improving resource efficiency. The results show that technological innovation is a key pillar in driving a green economy, but its successful adoption is highly dependent on appropriate government policy support. In addition, public education and awareness on the importance of green technologies are also crucial factors in accelerating the transition to a more sustainable economy. By integrating technology, policy and education, this research emphasises the importance of a holistic approach to achieving global sustainability goals.